Age-related timing of Short-toed Snake Eagle Circaetus gallicus migration along detoured and direct flyways. Issue 1 (2nd January 2017) - Agostini, Nicolantonio; Baghino, Luca; Vansteelant, Wouter M.G.; Panuccio, Michele
ABSTRACT: Capsule: Juvenile Short-toed Snake Eagles Circaetus gallicus hatching in the peripheral populations of Greece and Italy have limited opportunities for social learning of migration routes compared to those hatched elsewhere. Aims: To test the prediction that there would be a higher degree of migration synchrony between adult and juvenile Short-toed Snake Eagles originating from peripheral populations and using an extremely detoured flyway, when compared to other populations using a direct overland flyway. Methods: We use linear regression models to compare seasonal changes in the age distribution of migrating Short-toed Snake Eagles counted at two migration watch-sites in Italy (Arenzano) and Georgia (Batumi), along a detoured and a direct flyway, respectively. Results: Juveniles migrated a few days later than adults at both sites and the age ratios recorded at these two sites was similar. The daily proportion of juveniles increased along a similar slope during the migration season, thus showing a similar degree of synchrony between the age classes on both flyways. Conclusions: Contrary to our hypothesis, juvenile and adult migration is not more synchronized in peripheral populations using a detoured flyway compared to a core population using a direct migration flyway. Our results suggest that juveniles do not learn detours to complete trans-Mediterranean migration from their parents, but from other elders.